PREPARING MATURE STAFF BY STRENGTHENING STUDENTS' INTERDISCIPLINARY KNOWLEDGE - Tursunova Feruza Djamshidovna (American Journals, 2023)
In this article, the project improves the quality of education, the formation of all kinds of competencies in students, not only getting good grades, but also the stimulation of good learning, the lessons are more lively, the stabilization of internal motivational perception, the traditional Transitioning from science to innovative education, ensuring the realization of the general principles of human development is highlighted.
Keywords: modern overlay. technology, motivation, productivity.